PENERAPAN METODE CLUSTERING DENGAN ALGORITMA K-MEANS PADA PENGELOMPOKAN JURUSAN DATA CALON SISWA BARU DI SMK AL-ISHLAH CIKARANG UTARA - Nopiyanto; Bahrul Ulum (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
Based on data on the results of new student admissions at the AL-ISHLAH vocational high school, it shows the number of students who have registered. For this reason, it is necessary to classify the selection of the Department of Expertise to determine the success of students in completing their studies. One example of data processing is by clustering. One of the data grouping algorithms is the K-Means Algorithm. Data on the test scores of new prospective students have been entered into the program input, then the program performs selection processing based on the highest score to the lowest value, the results of passing the selection will be in the K-Means Algorithm, and the results are in the form of value data clusters. Implementation of a system designed using Web programming, database using SQL. The forms of software that will be implemented consist of interface implementation, namely login, main menu, registrant data input display, value data input, admin data input, majors data input, period data input, selection process display, clustering process data display, display cluster report, registrant report display, registrant report display, pass selection display. And the cluster graph.